Interhypothalamic Adhesion: A Series of 13 Cases - Whitehead, M.T.; Vezina, G. (American Journal of Neuroradiology, 2014)
SUMMARY: Interhypothalamic adhesion is a newly described disease entity, characterized by an abnormal parenchymal band connecting the medial margins of the hypothalami across the third ventricle. Additional anomalies, including cleft palate, gray matter heterotopia, cerebellar hypoplasia, optic atrophy, hippocampal under-rotation, and white matter lesions, may coexist. The purpose of this clinical report is to describe the imaging findings from a series of 13 patients with interhypothalamic adhesions discovered on brain MR imaging. IHAinterhypothalamic adhesionSPGRspoiled gradient-recalled-echo